2019
DOI: 10.1080/15332640.2019.1657541
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol: from Mesopotamia to Modern Iraq

Abstract: Aims: An understanding of alcohol's place in Iraq's history and society can help inform alcohol policy responses in that country and other Muslim majority countries. This paper describes the history of alcohol in Iraq from ancient to modern times, with reflection on the challenges facing Iraqi youth today.Methods: A search was undertaken to identify peer reviewed and grey literature that describes alcohol-related practices, norms and values across the millennia in Iraq. A historical overview is provided of alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…No study reported on harm-reduction or treatment initiatives and measures in Iraq. Iraq has no clear written or implemented alcohol policy, strategy or harm reduction initiatives [6,11]. This is despite at least three studies from diverse cities showing young people dying or placing themselves and others at risk while under the influence of alcohol [20,24,28].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…No study reported on harm-reduction or treatment initiatives and measures in Iraq. Iraq has no clear written or implemented alcohol policy, strategy or harm reduction initiatives [6,11]. This is despite at least three studies from diverse cities showing young people dying or placing themselves and others at risk while under the influence of alcohol [20,24,28].…”
Section: Discussionmentioning
confidence: 99%
“…Iraq is a nation that has been exposed to international and civil war for the past four decades. Most of Iraq's population is under the age of 24 [5], and exposed to civil war, directly or through family or community involvement [6]. In addition, Iraqi young people are influenced by conflicting principles and cultures-that of their home cultures and religions and that which they are exposed to with no censorship on television, social and mass media [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations